2022
DOI: 10.1177/15385744211073903
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial Internal Carotid Artery Aneurysm in Pregnancy

Abstract: Isolated extracranial internal carotid artery aneurysms (EICAAs) are rare, accounting for only about .4–4% of all peripheral artery aneurysms. We present a case of an EICAA in a young pregnant patient. To our knowledge, this is the first case being reported of a true EICAA during pregnancy in a multiparous woman. A 25-year-old pregnant patient presented with a pulsatile left neck swelling. Radiological investigations and subsequent surgery during the first trimester confirmed a true saccular left ICA with a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…While the specific causes of ECA aneurysms are yet to be fully understood, atherosclerosis is the most frequently acknowledged cause among elderly patients, alongside other factors such as trauma, fibromuscular dysplasia, previous surgery, congenital and acquired malformation, infection, and radiation exposure 1–6 . There are articles suggesting that occurrence of the ECCA may be linked to body mass index 7 On the contrary, a false aneurysm can be caused by medical intervention, such as carotid endarterectomy, or as a result of trauma or dissection or spontaneously, including in children and pregnant women 8,9 . It has been observed that up to 13% of patients with EICAA exhibit bilateral EICAAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the specific causes of ECA aneurysms are yet to be fully understood, atherosclerosis is the most frequently acknowledged cause among elderly patients, alongside other factors such as trauma, fibromuscular dysplasia, previous surgery, congenital and acquired malformation, infection, and radiation exposure 1–6 . There are articles suggesting that occurrence of the ECCA may be linked to body mass index 7 On the contrary, a false aneurysm can be caused by medical intervention, such as carotid endarterectomy, or as a result of trauma or dissection or spontaneously, including in children and pregnant women 8,9 . It has been observed that up to 13% of patients with EICAA exhibit bilateral EICAAs.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 There are articles suggesting that occurrence of the ECCA may be linked to body mass index 7 On the contrary, a false aneurysm can be caused by medical intervention, such as carotid endarterectomy, or as a result of trauma or dissection or spontaneously, including in children and pregnant women. 8 , 9 It has been observed that up to 13% of patients with EICAA exhibit bilateral EICAAs. Additionally, multiple synchronous aneurysms, specifically intracranial ones, have been documented in approximately 15%–20% of patients diagnosed with EICAA.…”
Section: Introductionmentioning
confidence: 99%